Encyclopedia of Cancer - Schwab, Manfred (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The Encyclopedia of Cancer provides rapid access to focused information on all topics of cancer research for clinicians, research scientists and advanced students. Given the overwhelming success of the first edition, which appeared in 2001, and fast development in the different fields of cancer research, it has been decided to publish a second fully revised and expanded edition, following the principal concept of the first edition that has proven so successful. Recent developments are seeing a dynamic merging of basic and clinical science, with translational research increasingly becoming a new paradigm in cancer research. The merging of different basic and clinical science disciplines towards the common goal of fighting against cancer has long ago called for the establishment of a comprehensive reference source both as a tool to close the language gap between clinical and basic science investigators and as a platform of information for students and informed laymen alike. While the First Edition featured scholarly contributions from approximately 300 scientists/clinicians in one Volume, the Second Edition includes more than 1.000 contributors in 4 Volumes with an A-Z format of more than 7.000 entries. It provides definitions of common acronyms and short definitions of related terms and processes in the form of keyword entries. In addition, there are detailed essays, which provide comprehensive information on syndromes, genes and molecules, and processes and methods. Each essay is well-structured, with extensive cross-referencing between all entries. A panel of Field Editors, each an eminent international expert for the corresponding field, will ensure the presentation of timely and authoritative Encyclopedia entries. These new traits will meet the expectance that a wide community has towards a cancer reference works. The Encyclopedia of Cancer will be accessible both in print and online, and this information source will be of value to both the clinical and basic scientific community as well as to the public.